2017
DOI: 10.1111/itor.12398
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear scalarization in multiobjective optimization with a polyhedral ordering cone

Abstract: In this work, we consider a multiobjective optimization problem in which the ordering cone is assumed to be polyhedral. In this framework, we characterize proper efficient solutions through nonlinear scalarization and a kind of polyhedral dilating cones. The main results are based on a characterization of weak efficient solutions, for which no convexity hypotheses are required. Moreover, the construction of these dilating cones allows us to obtain scalarization results that are easier to handle, and attractive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…They also designed a Newton-type algorithm for solving it. Very recently, Gutiérrez et al [15,16] characterized the several kind of exact and approximate efficient solutions of a class of multiobjective optimization problems with partial order provided by a polyhedral cone. From a computational point of view, they showed that the results in [15,16] based on the ordering cone generated by some matrix are attractive.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…They also designed a Newton-type algorithm for solving it. Very recently, Gutiérrez et al [15,16] characterized the several kind of exact and approximate efficient solutions of a class of multiobjective optimization problems with partial order provided by a polyhedral cone. From a computational point of view, they showed that the results in [15,16] based on the ordering cone generated by some matrix are attractive.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, Gutiérrez et al [15,16] characterized the several kind of exact and approximate efficient solutions of a class of multiobjective optimization problems with partial order provided by a polyhedral cone. From a computational point of view, they showed that the results in [15,16] based on the ordering cone generated by some matrix are attractive. Using the partial order considered in [16], Hai et al [17] continued to investigating vector equilibrium problems with a polyhedral ordering cone.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sawaragi et al [1985] reduce the problem to finding Pareto efficient points of a set in the objective function's image space. More recently, for example, Gutierrez, et al [19] define a scalarization by perturbing the same matrix.…”
Section: Introductionmentioning
confidence: 99%
“…There are three main factors involved with the profit maximization of the company: waste minimization, surplus minimization, and cost minimization. Therefore, a multiobjective modelling and optimization (Boros, Fehér, Lakner, Niroomand, & Vizvári, 2016;Cardillo, Cascini, Frillici, & Rotini, 2013;Franco, Jablonsky, Leopold-Wildburger, & Montibeller, 2009;Ghasemi & Varaee, 2017;Gholizadeh & Baghchevan, 2017;Gutiérrez, Huerga, & Novo, 2018;Jablonsky, 2014;Jiménez, Bilbao-Terol, & Arenas-Parra, 2018;Kovács & Marian, 2002;Özmen, Karakaya, & Köksalan, 2018;Sanei, Mahmoodirad, Niroomand, Jamalian, & Gelareh, 2017;Taassori et al, 2015) is a suitable approach for incorporating the above-mentioned objectives. Furthermore, when some parameters of the problem have uncertain nature, it must be reflected in the model as well (Fullér, Canós-Darós, & Canós-Darós, 2012;Fullér & Majlender, 2004;Moloudzadeh, Allahviranloo, & Darabi, 2013;Niroomand, Mahmoodirad, Heydari, Kardani, & Hadi-Vencheh, 2017;Salahshour & Allahviranloo, 2013;Salmasnia, Khatami, Baradaran Kazemzadeh, & Zegordi, 2015;Taassori, Niroomand, Uysal, Hadi-Vencheh, & Vizvari, 2016;Wang, Zhou, Li, Zhang, & Chen, 2014).…”
mentioning
confidence: 99%